The psychometric properties of the Thai version of the Zuckerman–Kuhlman-Aluja personality questionnaire - Tinakon Wongpakaran; Nahathai Wongpakaran; Zsuzsanna Kövi (Scientific Reports)
Abstract The Five-Factor Model of personality traits has consistently demonstrated expected associations with features of psychiatric disorders, both within the general population and clinical settings. In pursuit of a more nuanced understanding, facet-level assessments like the Zuckerman–Kuhlman–Aluja Personality Questionnaire (ZKA-PQ) offer more profound insights into their facets. However, notably, the applicability of the ZKA-PQ to the Thai population remains untested. We hypothesized that the Thai version of the ZKA-PQ would demonstrate the validity of the construct as the original version. Consequently, we enrolled 1,382 participants, 71.3% female, with a mean age of 29.04 years (SD = 10.46). The assessments included the ZKA-PQ, the Perceived Stress Scale, the Core Symptom Index-Depression, and the Neuroticism Inventory. Our findings supported the ZKA-PQ’s overarching personality traits but not at the facet level. Aligned with observations in non-Western cultures, it became evident that the Sensation Seeking and Activity facets exhibited sensitivity to the Thai population’s dynamics. In light of these outcomes, further exploration is merited to enhance the appropriateness of the Thai ZKA-PQ. This pursuit could illuminate cultural nuances that shape personality traits and their interplay within the Thai context.